Resiko Yang Mempengaruhi Kejadian Penyakit Infeksi Saluran Pernapasan Akut Pada Balita - Fatmawati S; Muhammad Awal; Muhammad Rifai (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: One of the most common causes of death in children in developing countries is Acute Respiratory Infection. Objective: To determine the analysis of risk factors that influence the incidence of ARI in children under five. Methods: This type of case-control study is retrospective. Arungkeke Public Health Center, Jeneponti Regency, involving 96 respondents, where the case sample was 48 respondents and control was 48 respondents. The instrument of this research used a questionnaire. The analysis used univariate and bivariate analysis with (chi-square test). Results: showed age under five (p=0.505) and OR = 0.743, immunization status (p=0.003) and OR = 5,500 times at risk, mother's knowledge (p= 0.000) and OR = 9,000 times at risk, residential density (p = 0.308) and OR = 1.346 times at risk, nutritional status (p = 0.660) and OR 1.214 times at risk. Conclusion: that there is a relationship between immunization status, knowledge, occupancy density with the incidence of Upper Respiratory Tract Infection. Immunization officers make interesting and fun activities when Healthcare Center activities are held so that parents and toddlers are happy to come to Healthcare Center places